Design, optimization and testing of extruded aluminium profiles assembled by mechanical snap-fit. (July 2022) - Alric, Jean; Desrochers, Alain; Béland, Jean-François
Abstract: Aluminium is increasingly replacing steel in many structural applications, primarily for its lightness and corrosion resistance. Such replacement remains a challenge requiring careful design and sizing to compensate for the aluminium Young modulus, toward a comparable level of reliability or rigidity. To that end, for road transport or bridge applications, extrusions are typically used along with welded, bolted, riveted or adhesively assembled connections. Breaking free from this constraint by designing profiles that are assembled by mechanical clips, using the elasticity of aluminium, is therefore a sensible alternative from cost, performance, and assembly time viewpoints. This study is based on finite element analysis and sizing of assembly forces, strength for typical load cases and geometrical optimization. This work is conducted on SolidWorks for design and ANSYS for simulations with many adjustments between these two software programs. An experimental study is also carried out on custom made extrusions subjected to assembly, static, and fatigue tests. The overall objective of this work is to propose a sizing and testing methodology for extruded aluminium profiles assembled by mechanical snap-fit.